Androgen receptor degraders overcome common resistance mechanisms developed during prostate cancer treatment - Kregel, Steven; Wang, Chao; Han, Xin; Xiao, Lanbo; Fernandez-Salas, Ester; Bawa, Pushpinder; McCollum, Brooke L.; Wilder-Romans, Kari; Apel, Ingrid J.; Cao, Xuhong; Speers, Corey; Wang, Shaomeng; et al. (Neoplasia (New York, N.Y.), 2020)
Androgen receptor (AR) antagonists, such as enzalutamide, have had a major impact on the treatment of metastatic castration-resistant prostate cancer (CRPC). However, even with the advent of AR antagonist therapies, patients continue to develop resistance, and new strategies to combat continued AR signalling are needed. Here, we develop AR degraders using PROteolysis TArgeting Chimeric (PROTAC) technology in order to determine whether depletion of AR protein can overcome mechanisms of resistance commonly associated with current AR-targeting therapies. ARD-61 is the most potent of the AR degraders and effectively induces on-target AR degradation with a mechanism consistent with the PROTAC design. Compared to clinically-approved AR antagonists, administration of ARD-61 in vitro and in vivo results in more potent anti-proliferative, pro-apoptotic effects and attenuation of downstream AR target gene expression in prostate cancer cells. Importantly, we demonstrate that ARD-61 functions in enzalutamide-resistant model systems, characterized by diverse proposed mechanisms of resistance that include AR amplification/overexpression, AR mutation, and expression of AR splice variants, such as AR-V7. While AR degraders are unable to bind and degrade AR-V7, they continue to inhibit tumor cell growth in models overexpressing AR-V7. To further explore this, we developed several isogenic prostate cell line models in which AR-V7 is highly expressed, which also failed to influence the cell inhibitory effects of AR degraders, suggesting that AR-V7 is not a functional resistance mechanism for AR antagonism. These data provide compelling evidence that full-length AR remains a prominent oncogenic driver of prostate cancers which have developed resistance to AR antagonists and highlight the clinical potential of AR degraders for treatment of CRPC.